Implementation of Environmental Education Courses: Analysis of RPS and Student Learning Experiences - Muhammad Syahrul; Ine Arini; Marike Muskitta; Husnaini Bahri (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
This study aims to describe the implementation of Environmental Education (EE) courses for second-semester students in the Biology Education Study Program by examining the relationship between the Semester Learning Plan (SLP), lecturers teaching practices, and students learning experiences. This study employs a qualitative descriptive approach with data collection techniques including document analysis, interviews with lecturers, and student interviews. The analysis reveals that the EE curriculum structure incorporates learning outcomes based on ecological literacy and is implemented through active methods such as recycling projects and field trips to environmental institutions. Students demonstrated positive responses and began to exhibit changes in their attitudes toward the environment, though these changes were not yet fully consistent. The study also highlighted the importance of integrating sustainability values across courses and strengthening affective evaluation. In conclusion, the implementation of PLH contributes to the development of students ecological awareness and is relevant for expansion in biology teacher education.